2004
DOI: 10.1158/0008-5472.can-03-3383
|View full text |Cite
|
Sign up to set email alerts
|

A Serial Analysis of Gene Expression (SAGE) Database Analysis of Chemosensitivity

Abstract: Drug sensitivity and resistance has been most extensively studied in cell lines carried in tissue culture. Furthermore, cell lines have been widely used in testing new anticancer agents, despite the widely recognized observation that cell lines are more sensitive to cytotoxic drugs than are their corresponding solid tumors. We used the Serial Analysis of Gene Expression (SAGE) database to identify differences between solid tumors and cell lines, hoping to detect genes that could potentially explain differences… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
71
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(74 citation statements)
references
References 48 publications
3
71
0
Order By: Relevance
“…Together, these results indicate that the concentrations of extracellular Mg 21 and Ca 21 regulate a 2 b 1 integrin function on Type I collagen in vitro and suggest that divalent cation shifts could potentially influence the malignant phenotype of pancreatic cancer cells in the Type I collagen-rich local tumor microenvironment in vivo. [14][15][16][17]48,49 Consistent with our previous inhibition of adhesion studies using media containing normal divalent cation concentrations (1 mM Mg 21 /1.8 mM Ca 21 ), 20,26,41 the present studies demonstrate that antibodies directed against the a 2 b 1 integrin inhibit pancreatic cancer cell adhesion on Type I collagen in the presence of optimal divalent cation concentrations (3.5 mM Mg 21 /0.5 mM Ca 21 ) as well. For the first time, we also demonstrate that antibodies directed against the a 2 b 1 integrin also inhibit pancreatic cancer cell proliferation on Type I collagen.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Together, these results indicate that the concentrations of extracellular Mg 21 and Ca 21 regulate a 2 b 1 integrin function on Type I collagen in vitro and suggest that divalent cation shifts could potentially influence the malignant phenotype of pancreatic cancer cells in the Type I collagen-rich local tumor microenvironment in vivo. [14][15][16][17]48,49 Consistent with our previous inhibition of adhesion studies using media containing normal divalent cation concentrations (1 mM Mg 21 /1.8 mM Ca 21 ), 20,26,41 the present studies demonstrate that antibodies directed against the a 2 b 1 integrin inhibit pancreatic cancer cell adhesion on Type I collagen in the presence of optimal divalent cation concentrations (3.5 mM Mg 21 /0.5 mM Ca 21 ) as well. For the first time, we also demonstrate that antibodies directed against the a 2 b 1 integrin also inhibit pancreatic cancer cell proliferation on Type I collagen.…”
Section: Discussionsupporting
confidence: 85%
“…3,4,[6][7][8][9][10][11] These cations presumably exert their effects by binding to the 3-5 putative cation-binding domains located on all integrin a subunits, 12 and possibly by interacting directly with b subunits. 13 We have recently demonstrated that a 2 b 1 integrin-mediated pancreatic cancer cell adhesion to Type I collagen, an ECM protein shown to be highly upregulated in pancreatic cancer [14][15][16][17] and to promote the malignant phenotype in vitro and in vivo, [18][19][20][21][22][23][24][25] is promoted in 1.5 mM Mg 21 and inhibited in 1.5 mM Ca 21 , 21 and that the a 2 b 1 integrin from pancreatic cancer cell lysates bound specifically to Type I collagen by affinity chromatography in 3 mM Mg 21 , can be eluted with 3 mM Ca. 2126 These data are consistent with our previous observations regarding the a 2 b 1 integrin, Type I collagen, and the various cell types involved in cutaneous wound repair, [27][28][29] of which strong parallels to the pancreatic cancer paradigm have been described.…”
mentioning
confidence: 99%
“…Recent analyses using microarray and serial analysis of gene expression technology confirm those studies and point out the strong expression of many other ECM genes in pancreatic cancer as well (Iacobuzio-Donahue et al, 2003a, b;Binkley et al, 2004;Stein et al, 2004).…”
Section: Discussionmentioning
confidence: 84%
“…The previous demonstrations that type I collagen is clearly upregulated (Mollenhauer et al, 1987;Lohr et al, 1994;Shimoyama et al, 1995;Tani et al, 1997;Kuehn et al, 1999;Linder et al, 2001;Tempia-Caliera et al, 2002;Iacobuzio-Donahue et al, 2003a, b;Binkley et al, 2004;Stein et al, 2004), and mediates a malignant phenotype in pancreatic cancer in vivo (Armstrong et al, 2004;Bachem et al, 2005), correlates directly with our present in vitro observations, and are further extended by our demonstration that the a 2 b 1 integrin specifically regulates this type I collagen-mediated phenotype in multiple pancreatic cancer cell lines. These observations collectively suggest that targeting the a 2 b 1 integrin may have therapeutic value in the treatment of pancreatic cancer in vivo.…”
Section: Discussionmentioning
confidence: 93%
“…Tumors of the testis, breast, and ovaries are normally responsive to chemotherapy, whereas tumors originating in the colon, kidney, or liver are often more resistant. The variation in chemotherapy sensitivity determined by tissue of origin is reduced in cell lines (5). Large screening programs are using cell line panels to predict the chemotherapeutic efficiency of compounds to different tumor types (6), the key assumption being that the tumor cell lines are good experimental models for the tumors they derive from.…”
mentioning
confidence: 99%